1994
DOI: 10.1063/1.112413
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of diamond film formed on silicon wafer by hot-filament chemical vapor deposition method

Abstract: Very important evidence has been obtained by high-resolution cross-sectional electron microscopy (HREM) that diamond films prepared by the hot-filament chemical vapor deposition (HFCVD) method were grown epitaxially on the mirror-polished Si(100) substrate in a local area with surface biasing pretreatment. There is about a 7.3° angle between Si (100) and D(100) heteroepitaxial crystalline planes. The same type of twinnings (coherent twin boundaries of type, Σ=3) exist on and near the interface. High preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…For example, the HFCVD apparatus is much simpler, and it is much easier to enlarge the deposition area in HFCVD at a much lower cost. Recently, Yang et al 6 reported observation of localized epitaxy of diamond directly on Si͑001͒ through high resolution transmission electron microscope ͑HRTEM͒. This sheds some light on diamond heteroepitaxy on Si, but they did not acquire uniformly large area oriented diamond films.…”
Section: Synthesis Of Oriented Textured Diamond Films On Silicon Via mentioning
confidence: 95%
“…For example, the HFCVD apparatus is much simpler, and it is much easier to enlarge the deposition area in HFCVD at a much lower cost. Recently, Yang et al 6 reported observation of localized epitaxy of diamond directly on Si͑001͒ through high resolution transmission electron microscope ͑HRTEM͒. This sheds some light on diamond heteroepitaxy on Si, but they did not acquire uniformly large area oriented diamond films.…”
Section: Synthesis Of Oriented Textured Diamond Films On Silicon Via mentioning
confidence: 95%
“…However, crucially, diamond nucleation is also poor on smooth ␤-SiC, and biasing is also required for nucleation, 17 so this does not seem an adequate explanation. Also, Kubisch et al 10 find that SiC appears immediately, but that diamond nuclei only appear later with a-C, while Yang et al 18 …”
mentioning
confidence: 96%
“…͑4͒ by using the example of heteroepitaxial deposition of diamond film on ␤-SiC and Si. [12][13][14][15] From experimental observation it is found that, during the early stage deposition, ͑i͒ the shape of grains remains nearly congruent before impingement ͑Fig. 6͒; ͑ii͒ the major growth direction is ͗001͘, but four large ͕111͖ faces and five small ͕100͖ faces form the contour of the diamond crystal, as seen in Fig.…”
Section: Epitaxial Growth Of Crystalsmentioning
confidence: 99%